Crash deluxe - De Pierres, Marianne (London : Orbit, 2005)
This volume provides explosive action set in an ultra-violent future world controlled by the media.
Formerly CIP.
Keywords: Plessis, Parrish (Fictitious character) -- Fiction; Queensland -- Fiction; Science fiction